Study & Design of Water Therapy Development Tool ( Babw - Therapy 2.0 ) using nlp principal - Almary Bayan F.S (2023)
This report documents the project outline of my Final Year Project (FYP), the progress to date and future project plans. It also documented how the future plans will be undertaken in the most efficient way possible to meet all criteria of the project outline.